The Predisposing Factors to Communicate Effectively in Providing Drug Information - Ryo Hastama; Ni Nyoman Yudianti Mendra; Ni Putu Udayana Antari (Sanata Dharma University, 2025)
Effective communication in providing drug information is essential to achieve the expected outcome in implementing pharmaceutical care. This study aims to analyze factors that influence the occurrence of effective communication in providing drug information. Data were collected using a Likert-scale questionnaire survey technique with a cross-sectional design. The study involved 100 samples from all districts in Denpasar City, which were taken by convenience sampling technique. The characteristics of the respondents are described descriptively. Bivariate and multivariate tests are used to analyze the effect of independent variables on effective communication. The pharmacy atmosphere has no significant impact on effective communication. Pharmacists' technical and interpersonal communication skills can facilitate effective communication on the Chi-squared test, but only the interpersonal communication competencies of pharmacists can encourage effective communication in the logistic regression analysis (p-value 0.008; CI: 95%; OR 4.751: 1.492-15.133). Communication factors, in general, predispose to effective communication. Besides paying attention to the message's contents, pharmacists must pay more attention to how drug information is conveyed to patients. Thus, there is a common understanding between the communicator and the communicant. The patient will also be encouraged to use the drug according to the instructions given so that the ultimate goal of treatment can be achieved.